Inclusive health care for LGBTQ+ youth: support, belonging, and inclusivity labour. Issue 4 (8th August 2021) - Newman, Christy E.; Prankumar, Sujith Kumar; Cover, Rob; Rasmussen, Mary Lou; Marshall, Daniel; Aggleton, Peter
ABSTRACT: Drawing on findings from a study of two social generations of gender and sexuality diverse Australians, this paper offers a critical analysis of expectations and experiences of inclusive health care for LGBTQ+ youth. Data were collected by means of individual and focus group interviews with people from two different social generations who grew up in regional or urban Australia: those born in the 1970s (n = 50) and those born in the 1990s (n = 71). Data were analysed inductively to develop insights into what inclusive health care meant, and what this revealed about the potential for fostering belonging in healthcare settings. Findings raise critical questions about how inclusiveness of care might best be understood in encounters between gender and sexual minorities and health professionals. In particular, forms of 'inclusivity labour' were observed across the social generations, both in terms of the work involved in seeking to locate supportive services, and in assessing the performance of clinicians in healthcare settings, with implications for the continued engagement of LGBTQ+ young people with essential forms of care. Mobilising contemporary forms of inclusivity labour, including attention to the affective dimensions of healthcare engagement, has the potential to promote both better health and more meaningful experiences of belonging for gender and sexual minorities.